Mandapa of the Sitaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The mandapa (pillared hall) of the Sitaleshwar Temple is square in design with a large number of pillars—26 in total, according to the Archaeological Survey of India (ASI). The pillars are carved with purnaghata kalasha, an auspicious motif that symbolizes abundance, growth, and prosperity. The shafts of the pillars are carved with grassamukha (kirtimukha or face of glory) and chain motifs.